2010
DOI: 10.1128/aem.01895-09
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lactobacillus sobrius/L. amylovorus as a New Microbial Marker of Pig Manure

Abstract: Based on a comparison of the dominant microbial populations in 17 pig manure samples and using a molecular typing method, we identified a species, Lactobacillus sobrius and Lactobacillus amylovorus (which now are considered a single species and are designated L. sobrius/amylovorus here), that was consistently found in manure. The aim of the present study was to confirm by real-time PCR the relevance of this species as a marker of pig fecal contamination. The specificity of L. sobrius/amylovorus was evaluated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 42 publications
4
33
0
2
Order By: Relevance
“…However, pig pasturing has not been reported or observed on the Daoulas catchment. Separately, Lactobacillus amylovorus GE39/GE40, another pig-associated marker (19), was quantified at concentrations ranging from 4.6 to 6.5 log 10 copies/100 ml in 5 out of the 5 water samples collected downstream of the accidental spillage monitored in the present study (Olivia Solecki, Irstea, Rennes, France, personal communication). This marker has a greater persistence than Pig2Bac in fresh and marine waters (32) and might be considered for pig manure tracking at the catchment level.…”
Section: Discussionmentioning
confidence: 87%
“…However, pig pasturing has not been reported or observed on the Daoulas catchment. Separately, Lactobacillus amylovorus GE39/GE40, another pig-associated marker (19), was quantified at concentrations ranging from 4.6 to 6.5 log 10 copies/100 ml in 5 out of the 5 water samples collected downstream of the accidental spillage monitored in the present study (Olivia Solecki, Irstea, Rennes, France, personal communication). This marker has a greater persistence than Pig2Bac in fresh and marine waters (32) and might be considered for pig manure tracking at the catchment level.…”
Section: Discussionmentioning
confidence: 87%
“…L. amylovorus was a stable member of the Lactobacillus community and it was not affected by any of the diets investigated. The prevalence of this species in pig faeces coincides with its use as a microbial marker of pig manure (Marti et al, 2010). Konstantinov et al (2004) demonstrated that the combination of dietary fibre and oligosaccharides present in the diet may specifically stimulate the L. amylovorus-like population along the gut of weaning pigs.…”
mentioning
confidence: 85%
“…As a result, many assays with host-specific primer sets do not have reliable specificities for identifying and quantifying fecal pollution sources (McLain et al, 2009), which requires alternative fecal indicators to increase the choice of tools and accurately identify the fecal pollution source in water (Marti et al, 2010).…”
mentioning
confidence: 99%